2020
DOI: 10.1021/acs.inorgchem.0c00007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study for the Cobalt(II)- and Iron(II)-Mediated Desulfurization of Disulfides Demonstrating That the C–S Bond Cleavage Step Precedes the S–S Bond Cleavage Step

Abstract: A unique Co(II)-and Fe(II)-mediated complete desulfurization of disulfides of the type RS-SR and RC(O)S-SC(O)R to yield the corresponding alcohols (ROH) and carboxylic acids (RCOOH), respectively, along with the formation of a dicobalt(II)/diiron(II)− hydrosulfide complex, [M 2 (PhBIMP)(μ 2 -SH)(DMF)] 2+ (M = Co, Fe), has been demonstrated. This new desulfurization reaction involves cleavage of both C−S and S−S bonds, where the cleavage of the S−S bond (presumably two-electron reduction of the S−S bond) may ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
3
20
1
Order By: Relevance
“…These results demonstrate that, unlike the clean and facile C–S bond cleavage reaction mediated by Co­(II) , and Fe­(II), , the reaction of a series of thiolates with hydrated Ni­(II) salt leads to the formation of both the dinickel­(II)–thiolate and dinickel­(II)–hydrosulfide complexes, of which the latter complex is generated via the hydrolytic C–S bond cleavage of coordinated thiolates in the former complex. In our previous studies , involving Fe­(II) and Co­(II), we have shown that the C–S bonds of thiolates are cleaved hydrolytically, and such C–S bond cleavage reactions are mediated by solvent coordinated dinuclear Fe­(II)/Co­(II) complexes ( A in Scheme ) in the presence of a base, such as Et 3 N. The proposed working mechanism considered the initial formation of a dinuclear Fe­(II)/Co­(II)–solvento complex (solvent = DMF/H 2 O) followed by its conversion to a dinuclear Fe­(II)/Co­(II) complex featuring a coordinated thiolate and water molecule/molecules ( B in Scheme ) which finally leads to the hydrolyzed organic product (alcohol) and diiron­(II)/dicobalt­(II)–hydrosulfide complexes ( C in Scheme ). The generation of the dinuclear Fe­(II)/Co­(II)–solvento complexes (initial complexes generated in the reaction solution) and the dinuclear Fe­(II)/Co­(II)–hydrosulfide complexes (final products) in the proposed working mechanism (Scheme ) was confirmed by molecular structure determinations and mass spectrometric study, ,, while the dinuclear intermediate featuring a coordinated thiolate and water molecule ( B in Scheme ) has been supported so far by only a mass spectrometric study .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrate that, unlike the clean and facile C–S bond cleavage reaction mediated by Co­(II) , and Fe­(II), , the reaction of a series of thiolates with hydrated Ni­(II) salt leads to the formation of both the dinickel­(II)–thiolate and dinickel­(II)–hydrosulfide complexes, of which the latter complex is generated via the hydrolytic C–S bond cleavage of coordinated thiolates in the former complex. In our previous studies , involving Fe­(II) and Co­(II), we have shown that the C–S bonds of thiolates are cleaved hydrolytically, and such C–S bond cleavage reactions are mediated by solvent coordinated dinuclear Fe­(II)/Co­(II) complexes ( A in Scheme ) in the presence of a base, such as Et 3 N. The proposed working mechanism considered the initial formation of a dinuclear Fe­(II)/Co­(II)–solvento complex (solvent = DMF/H 2 O) followed by its conversion to a dinuclear Fe­(II)/Co­(II) complex featuring a coordinated thiolate and water molecule/molecules ( B in Scheme ) which finally leads to the hydrolyzed organic product (alcohol) and diiron­(II)/dicobalt­(II)–hydrosulfide complexes ( C in Scheme ). The generation of the dinuclear Fe­(II)/Co­(II)–solvento complexes (initial complexes generated in the reaction solution) and the dinuclear Fe­(II)/Co­(II)–hydrosulfide complexes (final products) in the proposed working mechanism (Scheme ) was confirmed by molecular structure determinations and mass spectrometric study, ,, while the dinuclear intermediate featuring a coordinated thiolate and water molecule ( B in Scheme ) has been supported so far by only a mass spectrometric study .…”
Section: Resultsmentioning
confidence: 99%
“…However, synthesis of a dinickel­(II)–thiolate complex using a simple, monodentate thiolate remained to be achieved. Considering these results and the known difficulty experienced in the case of C–S bond cleavage of aromatic thiolates (such as NaSPh) as compared with the facile C–S bond cleavage reactions for the aliphatic thiolates (such as NaSR; R = Me, Et, t Bu), ,, the reaction of NaSPh with Ni­(ClO 4 ) 2 ·6H 2 O was therefore performed with the expectation of preparing the benzenethiolate coordinated dinickel­(II) compound as the sole product. Indeed, reaction of Ni­(ClO 4 ) 2 ·6H 2 O and HBPMP with NaSPh in the presence of Et 3 N in DMF for 12 h yielded the desired compound, [Ni 2 (BPMP)­(SPh)­(DMF)­(MeOH)­(H 2 O)]­(ClO 4 ) 2 ( 7 (ClO 4 ) 2 ) (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us begin with the relatively simple example of C−S bond photodissociation, which can be important in astrochemistry, 32 biomedicine, 33 and catalysis. 34 For C−S single bond dissociation, nonradiative internal conversion between the first excited state 1 ππ* and the dissociative 1 πσ* state is key. 35 Here, we instead investigate the C−S double bond dissociation of thioacetone, (CH 3 ) 2 CS, using both SA-CASSCF and SS-CASSCF.…”
Section: Resultsmentioning
confidence: 99%
“…Let us begin with the relatively simple example of C–S bond photodissociation, which can be important in astrochemistry, biomedicine, and catalysis . For C–S single bond dissociation, nonradiative internal conversion between the first excited state 1 ππ* and the dissociative 1 πσ* state is key .…”
Section: Results and Discussionmentioning
confidence: 99%